Sosialisasi Layanan Digital Diskominfo dalam Upaya Peningkatan Akses Informasi dan Pengaduan Masyarakat di Kabupaten Kediri - Huda, M Thoriqul; Mu’asyaroh, Rif’atul; Sari, Dewi Pancasila; Amrulloh, Abduzzaki (LP2M Institut Agama Islam Ngawi, 2026)
Public information transparency is an essential aspect in realizing a transparent, accountable, and participatory government. The Department of Communication and Informatics (Diskominfo) of Kediri Regency conducted a socialization program on digital-based information and complaint services at UIN Syekh Wasil Kediri, involving internship students as the documentation team. This activity aimed to introduce the E-PPID and SP4N-LAPOR mechanisms while enhancing the digital literacy of the academic community. The approach applied was the Asset-Based Community Development (ABCD) method, which focuses on utilizing local assets such as human resources, digital infrastructure, and students’ technical skills through the stages of Discovery, Dream, Design, Define, and Destiny. Observational results indicate that the documentation activities carried out by students contribute to expanding the reach of public information through digital publications. This activity is expected to serve as a foundation for sustainable collaboration between local government and higher education institutions to strengthen inclusive access to public information.